Second Suburethral Sling Implantation for the Recurrent Urinary Incontinence after Radical Prostatectomy when First Sling Surgery was Non-Effective: Case Report - Černiauskienė, Aušra; Rimaitė, Ieva (Lietuvos chirurgija, 2023)
Stress urinary incontinence is a complication after radical prostatectomy. The suburethral sling implantation operation is often performed for mild to moderate male urinary incontinence after radical prostatectomy. There are non-adjustable suburethral slings that are effective up to 73.7% and adjustable slings that are effective up to 92%. We present a case report of a 62-year-old man who underwent radical prostatectomy due to prostate cancer in 2018 and experienced moderate degree urinary incontinence. After non-effective conservative treatment in 2020-02-27, the suburethral transobturator sling implantation was performed in another hospital, but it did not yield effective results. After further examinations in 2023-03-25, an adjustable ATOMS system suburethral male sling implantation was performed and it was effective. 2023-05-03 ATOMS system was adjusted and after this there was no urinary incontinence. ATOMS system is an effective surgical method for the treatment of male recurrent urinary incontinence or for cases where the initial sling implantation has failed.